Distributed source coding : theory, algorithms, and applications - Dragotti, Pier Luigi; Gastpar, Michael (Academic Press/Elsevier, 2009)
The advent of wireless sensor technology and ad-hoc networks has made DSC a major field of interest. Edited and written by the leading players in the field, this book presents the latest theory, algorithms and applications, making it the definitive reference on DSC for systems designers and implementers, researchers, and graduate students. This book gives a clear understanding of the performance limits of distributed source coders for specific classes of sources and presents the design and application of practical algorithms for realistic scenarios. Material covered includes the use of standard channel codes, such as LDPC and Turbo codes, to DSC, and discussion of the suitability of compressed sensing for distributed compression of sparse signals. Extensive applications are presented and include distributed video coding, microphone arrays and securing biometric data. This book is a great resource covering the breadth and depth of distributed source coding that's appropriate for everyone from theoreticians to practitioners. - Richard Baraniuk, Rice University *Clear explanation of the principles of distributed source coding (DSC), a technology that has applications in sensor networks, ad-hoc networks, and distributed wireless video systems for surveillance *Edited and written by the leading players in the field, providing a complete and authoritative reference *Contains all the latest theory, practical algorithms for DSC design and the most recently developed applications.